A fuzzy cognitive map system to explore the repercussions of Greek PSI and Bank recapitalization on the Cyprus economy - Papaioannou, Maria C.; Neocleous, Costas; Papageorgiou, Charalambos; Schizas, Christos N. (My University, 2014)
Recently, Greece experienced a serious financial crisis that forced the country to sign a bailout memorandum with Troika (European Commission, International Monetary Fund and European Central Bank who formed a group of international lenders that laid down stringent austerity measures when they provided bailouts for indebted European states). The term Troika, which comes from the Russian meaning 'group of three', was increasingly used during the recent Eurozone crisis. In February of 2012, the country proceeded to a second bailout package. At the same time a debt restructuring was applied, that included a private sector involvement (PSI) that resulted in 75% overall loss. Due to the strong economic ties between Greece and Cyprus, PSI had a substantial impact on the Cypriot economy. A fuzzy cognitive map (FCM) system has been developed and used to study the repercussions of the Greek PSI on the economic dynamics of Cyprus and more specifically on the Cypriot banking sector. A novel FCM methodology has been used as regards to the proper identification, definition and initialization of the concepts and sensitivities, as well as on the updating rule. Different scenarios were implemented aiming to examine how certain core factors of Cyprus economy interact with Greek PSI and between them. The results were confirmed by comparing them with the actual events. Thus, they proved to be very promising and justify the usefulness of FCM for this particular kind of problems.
Keywords: Banking systems; Cyprus economy; Fuzzy cognitive maps; Intelligent systems